MACROFAUNA EPIEDÁFICA EM ADUBOS VERDES ANTERIOR A CULTURA DO ALGODOEIRO - TEZOLIN, Thiara de Azevedo; SOUZA, Elen Regina Cáceres; TORRES, Francisco Eduardo; ABOT, Alfredo Raul; JUNQUEIRA, Patrícia Helena (ANAIS DO ENIC, 2018)
-